2005
DOI: 10.1016/j.cardiores.2004.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Tenascin-C is an essential factor for neointimal hyperplasia after aortotomy in mice

Abstract: We have presented direct evidence that tenascin-C is a crucial molecule in neointimal hyperplasia at anastomotic sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 21 publications
0
51
0
Order By: Relevance
“…Cilostazol inhibited not only PDGF-induced SMC proliferation, but also TNC mRNA expression induced by PDGF in cultured aortic SMCs [17]. We also demonstrated that neointimal formation at suture sites after aortotomy in TNC-deficient mice was noticeably reduced compared to that in wild-type [18]. TNC may be a prime target for therapy in suppressing neointimal hyperplasia after vascular surgery.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…Cilostazol inhibited not only PDGF-induced SMC proliferation, but also TNC mRNA expression induced by PDGF in cultured aortic SMCs [17]. We also demonstrated that neointimal formation at suture sites after aortotomy in TNC-deficient mice was noticeably reduced compared to that in wild-type [18]. TNC may be a prime target for therapy in suppressing neointimal hyperplasia after vascular surgery.…”
Section: Introductionmentioning
confidence: 58%
“…Although marked expression of TNC has been found in various vascular lesions in active phases [3,4,6,7], its functional significance during the development of neointimal hyperplasia remains obscure. We recently demonstrated the contribution of TNC to neointimal hyperplasia in a simple aortotomy model using TNCdeficient mice [18]. In this regard, we carried out the present study to elucidate the direct contribution to stenosis of free artery graft transplantation using TNC-deficient mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1-4 Following vascular injury, however, ECM-degrading matrix metalloproteinases (MMPs) remodel the preexisting ECM to create a tissue microenvironment that is conducive for SMC proliferation, migration, and survival. [3][4][5] Understanding how alterations in adhesive interactions within the vascular ECM modify SMC behavior, therefore, represents an important question in vascular pathobiology.Tenascin-C (TN-C) is an ECM glycoprotein induced within remodeling hypertensive pulmonary arteries (PAs), 6 -10 as well as in systemic, obliterative vasculopathies, [11][12][13] where it supports vascular SMC proliferation, migration, and survival. 4,14,15 In keeping with the idea that TN-C plays a direct role in promoting vascular disease, studies using TN-C null mice demonstrate that these animals are refractory to neointimal hyperplasia after aortotomy.…”
mentioning
confidence: 99%
“…94 The involvement of TN-C in the intimal hyperplasia of occlusive/stenotic vascular disease has also been extensively studied. Intimal hyperplasia is defined as excessive migration and proliferation of SMCs 22 Therefore, TN-C may be a target molecule for controlling stenotic neointimal formation. Recent drug-eluting stents have remarkably reduced the rate of restenosis and, at the same time, have created a need for more precise evaluation of pathological change of the lesion combined with vascular imaging.…”
Section: Tn-c In the Vascular Systemmentioning
confidence: 99%